Pengaruh Impersonalitas Terhadap Kepuasan Masyarakat di RSUD Syeh Yusuf Kabupaten Gowa - Hardianti Hardianti; Nuryanti Mustari; Hafiz Elfiansya Parawu (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2018)
The purpose of this study is to know the influence of impersonality onpublic satisfaction in RSUD Syekh Yusuf Gowa Regency. This research used quantitative method with survey type using simple random sampling with measurement of research instrument is done by likert scale. The data analysis technique research was descriptive statistical analysis techniques and simple regression analysis techniques with the help of SPSS version 21 software applications. The results found that Impersonalities impact on Public Satisfaction in RSUD Syeh Yusuf Gowa Regency using Simple Regression Equation Model concluded that, the value of Constant (a) amounted to5,475, meaning if Impersonality (X) value 0, then the result of Public Satisfaction (Y) the value was positive that is 5,475. And increasing the value of Impersonality (X) then the value of Public Satisfaction (Y) will increase means there was influence between Impersonalities and Public Satisfaction in RSUD Syeh Yusuf Gowa Regency. Role (R Square) Impersonality (X) on Public Satisfaction (Y) in RSUD Syeh Yusuf Gowa Regency, hence R Square value amounted to 0,520 or 52%. Thus, Impersonality (X) has an influence on Public Satisfaction (Y) in RSUD Syeh Yusuf Gowa Regency amounted to 52%, while the rest amounted to 48% obtained from 100% - 52% = 48% unobserved variables.